Digital Transformation of Employee Experience Management: Tools, Practices, and Trends - Oksana Kravchuk; Iryna Varis; Ivanna Liaсh (Journal of Vasyl Stefanyk Precarpathian National University)
The article focuses on the digital transformation of Employee Experience Management (EXM) in the context of global business process digitalization. The research aims to systematize and scientifically substantiate modern approaches to the digital transformation of EXM, identify key tools, analyze successful implementation practices, and identify promising development trends. The research employs various methods, including general scientific techniques, specialized cognitive methods, analysis, synthesis, and comparative analysis. The study resulted in a systematization of theoretical and methodological foundations of EXM in the digital economy, development of the classification of digital EXM tools by functional purpose, analysis of the modern EXM software market, identification of digital transformation trends in EXM, development of a metrics system for assessing the impact of digital tools on employee experience, identification of challenges in implementing digital tools and proposed ways to overcome them. The scientific novelty of the research lies in the first comprehensive classification of digital EXM tools by functional purpose, the improvement of approaches to evaluating digital tools' effectiveness through the development of the KPI system, the advancement of conceptual foundations of digital transformation of employee experience, and the deepened understanding of digital technologies' impact on HR processes transformation. The formed recommendations for selecting and implementing digital solutions can be readily applied to HR departments. The proposed metrics allow for evaluating the effectiveness of implemented digital tools and their impact on employee experience. Research results create a foundation for developing digital transformation strategies in the HR sphere.